Fracture resistance analysis of PEEK-polymer. Issue 4 (2nd October 2017) - Lesiuk, Grzegorz; Sawicka, Aleksandra; Correia, José; Frątczak, Roman
Abstract: PEEK is a thermoplastic polymer with halfcrystallic structure – the scientific name of this material is poly(oxy-1, 4-phenylene-oxy-1, 4-phenylenecarbonyl-1, 4-phenylene). It has a high melt and glass transition temperatures (Tm = 340 °C, Tg = 143 °C), high chemical resistance and is melt processable. Thus it has been used in a variety of structural and insulation applications. Nowadays, one of them is the biomedical application. The mechanical properties of PEEK have been extensively investigated in many research papers. However, there is not so high number of papers devoted to the fracture susceptibility of PEEK-material. Therefore, the the aim of this work is to present the results of studies on PEEK material with the use of fracture toughness test and digital image correlation. In order to conduct the tests, there were used two types of samples: SENB and CT. In comparison with other polymeric materials subjected to biomedical application, PEEK material presents relatively good fracture resistance with their biocompatibility.